(untitled) (Baghdad Science Journal, 2019)
The accurate extracting, studying, and analyzing of drainage basin morphometric aspects is important for the accurate determination of environmental factors that formed them, such as climate, tectonic activity, region lithology, and land covering vegetation. This work was divided into three stages; the 1st stage was delineation of the Al-Abiadh basin borders using a new approach that depends on three-dimensional modeling of the studied region and a drainage network pattern extraction using (Shuttle Radar Topographic Mission) data, the 2nd was the classification of the Al-Abiadh basin streams according to their shape and widenings, and the 3rd was extracting then taking up the quantitative analysis technique to estimate the basin morphometric aspects and the basin’s environmental parameters that created them. The Al-Abiadh valley basin is a six-order one with a dendritic, parallel, and deranged drainage network. The flood hazard is absent at the basin mouth because the valley runoff takes a long time to reach the sink (Al-Razaza Lake), located in the middle part of Iraq, with a low flow peak due to the high permeability soil, the arid to semi-arid climate, and the low annual precipitation rate. The region studied is an alluvial basin with similar geological structural solidity in most places. The drainage network was found to be controlled by lineaments and fracture traces; the basin has passed its youth geomorphic phase.